2017
DOI: 10.1017/s1463423617000573
|View full text |Cite
|
Sign up to set email alerts
|

The provider perspective: investigating the effect of the Electronic Patient-Reported Outcome (ePRO) mobile application and portal on primary care provider workflow

Abstract: Aim: This qualitative study investigates how the Electronic Patient-Reported Outcome (ePRO) mobile application and portal system, designed to capture patient-reported measures to support self-management, affected primary care provider workflows. Background: The Canadian health system is facing an ageing population that is living with chronic disease. Disruptive innovations like mobile health technologies can help to support health system transformation needed to better meet the multifaceted needs of the comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
71
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(73 citation statements)
references
References 43 publications
1
71
1
Order By: Relevance
“…Healthcare professionals have better insight into the disease activity and identification of issues that may have previously gone undetected 48. For example, healthcare professionals using a mobile-based PROM system for patients with complex needs reported that PROMs provided them with additional information on patients’ wellbeing 52…”
Section: Improvements In Clinical Practicementioning
confidence: 99%
See 3 more Smart Citations
“…Healthcare professionals have better insight into the disease activity and identification of issues that may have previously gone undetected 48. For example, healthcare professionals using a mobile-based PROM system for patients with complex needs reported that PROMs provided them with additional information on patients’ wellbeing 52…”
Section: Improvements In Clinical Practicementioning
confidence: 99%
“…In a review of qualitative research on clinicians’ experiences of using PROMs, clinicians thought PROMs can impact on processes of care, such as communication, shared decision-making and care planning 55. Evaluations of PROMs in routine clinical practice have reported improvements in patient-clinician communication in a variety of settings including oncology56 and patients with complex healthcare needs 52…”
Section: Improvements In Clinical Practicementioning
confidence: 99%
See 2 more Smart Citations
“…According to Gallagher et al (2015), patientcenteredness is key to effective treatment of chronic diseases, which entails involving patients more directly in the treatment process. Regularly registering patient data improves the quality of diagnoses and treatment, partly because healthcare professionals are able to adapt plans based on PRO data [6]. PRO data opens up new possibilities, and studies have shown the value of utilizing such data with regard to making early diagnoses and freeing up resources [10].…”
Section: Background Literaturementioning
confidence: 99%